1989
DOI: 10.1111/j.1469-8986.1989.tb03155.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Miscuing, Electrodermal Activity, and the Allocation of Processing Resources

Abstract: The present research investigated the effects of stimulus miscuing on electrodermal responding, dishabituation, stimulus expectancy, and the allocation of processing resources as assessed by reaction time to a secondary task probe stimulus. In both experiments, a control group received 33 S1-S2 pairings intermixed with 33 S3-alone presentations. For the experimental group, S2 was miscued by its presentation following S3 on 4 trials. Experiment 1 (N = 24) demonstrated reliable electrodermal responding when S2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 15 publications
7
9
0
Order By: Relevance
“…Our results are also consistent with recent reports of interaction between elementally trained cues (e.g., Escobar, Arcediano, & Miller, 2001;Escobar, Matute, & Miller, 2001;Matute & Pineño, 1998a, 1998b, as well as with several reports that show interaction between cues that have received differential (i.e., elemental) inhibition training (e.g., Lipp et al, 1993;Packer & Siddle, 1989;Siddle, 1985;Siddle et al, 1990). Moreover, some of the comparisons of the elemental and compound inhibition procedures that have been reported in the literature are also consistent with the results of Experiment 1.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are also consistent with recent reports of interaction between elementally trained cues (e.g., Escobar, Arcediano, & Miller, 2001;Escobar, Matute, & Miller, 2001;Matute & Pineño, 1998a, 1998b, as well as with several reports that show interaction between cues that have received differential (i.e., elemental) inhibition training (e.g., Lipp et al, 1993;Packer & Siddle, 1989;Siddle, 1985;Siddle et al, 1990). Moreover, some of the comparisons of the elemental and compound inhibition procedures that have been reported in the literature are also consistent with the results of Experiment 1.…”
Section: Discussionsupporting
confidence: 82%
“…For example, several researchers have reported attenuated responding to a target cue, X, if a series of X-O pairings intermixed with A-no-O trials are followed by one or more A-O trials (Lipp & Dal Santo, in press;Lipp, Siddle, & Dall, 1993;Packer & Siddle, 1989;Siddle, 1985;Siddle, Broekhuizen, & Packer, 1990). In these studies, the outcome is miscued during Phase 2 by the cue that predicts its absence (A).…”
mentioning
confidence: 99%
“…Nevertheless, there are some observations in the literature that could be interpreted as convergent and some that could be interpreted as inconsistent with the present findings. Convergent data can be found in the "miscuing effect" literature (e.g., Lipp, Siddle, & Dall, 1993;Packer & Siddle, 1989). The miscuing effect refers to impaired responding that occurs when the US is "miscued" by an inhibitory stimulus (i.e., A+ training experienced after X+/A -training produces impaired responding to X).…”
Section: Methodsmentioning
confidence: 82%
“…Other researchers have examined the sensitivity of SCRs to variations in single-and dual-task difficulty and concluded that while nonspecific manifestations of EDA are sensitive to general levels of arousal, SCRs appear to provide a more specific index of human information processing. For instance, Packer and Siddle (1989;see also Siddle & Packer, 1987) found that deviations in a train of repeated stimuli elicited larger SCRs and increased secondary task probe RTs than repeated stimuli. Dawson, Schell, Beers, and Kelly (1982) found that reinforced classically conditioned stimuli (CS+) elicited larger SCRs and slower probe RTs than CS-stimuli and that miscued USC-CS pairs also resulted in delayed probe RTs and large SCRs.…”
Section: Sensitivity and Diagnosticitymentioning
confidence: 93%